Efektivitas Model TSTS Berbasis Gambar Berseri terhadap Hasil Belajar PPKn - Suci Yarti; Edy Herianto; Edy Kurniawansyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
his study aims to examine the effectiveness of the Two Stay Two Stray (TSTS) cooperative learning model based on serial images on student learning outcomes in Pancasila and Civic Education (PPKn) subjects. The method used is quantitative research with a pretest-posttest control group quasi-experimental design. The sample consisted of two classes, namely the experimental class (VIII-2) which received treatment using the TSTS model with serial images, and the control class (VIII-1) with conventional learning. The test instruments consisted of multiple-choice questions that had been validated and were reliable. Data analysis included normality, homogeneity, and independent t-tests. The results showed a significance value of 0.002 < 0.05, with the average score of the experimental class (90.00) higher than that of the control class (85.27). In conclusion, the TSTS learning model based on serial images was effective in improving the Civic Education learning outcomes of eighth-grade students. This study recommends the use of this model as an innovative and interesting learning alternative for students.